Reconstructing Larix sibirica dynamics based on dendroclimatology: century-scale simulation of growing season NDVI and future tree growth projections - che, Jing; Ye, Mao; Xu, Xingbin; Zeng, Guoyan; Lv, Yexin; Chen, Weilong; Li, Miaomiao; Xie, Xiaodong; Wang, Tongxin (Frontiers in Forests and Global Change, 2026)
Tree-ring width records provide crucial insights into historical vegetation dynamics and climate change. This study integrates tree-ring width index (RWI), MODIS NDVI remote sensing data, and 11 monthly extreme climate indices from Larix sibirica Ledeb. chronologies in the Burqin and Two-River Source regions of the Altai Mountains, Xinjiang, to investigate tree-ring-NDVI relationships and reconstruct vegetation coverage since the 19th century. Using LASSO regression to identify dominant extreme climate drivers and CMIP6 future climate scenarios, we projected radial growth trends and potential tree decline risks. Results demonstrate significant positive correlations between RWI and growing-season NDVI (p < 0.05), reflecting tree-ring sensitivity to vegetation productivity changes. Pettitt tests revealed significant pre-mutation declining trends in historical vegetation coverage at both sites. Pearson correlation analysis revealed distinct response patterns of tree-ring width to extreme climate events between the two sampling sites. At the Burqin site, extreme precipitation during the previous autumn (October RX1day) significantly constrained radial growth. Conversely, elevated daytime temperatures (TX90p), greater diurnal temperature ranges (DTR) prior to the growing season, and short-duration heavy precipitation events (RX5day) during transitional periods and critical growth months exerted positive effects on tree growth. The Two-River Source site exhibited contrasting responses: anomalously warm autumn conditions (TN90p) following the previous growing season led to subsequent growth suppression. Extreme temperature events during the current year demonstrated dual effects - while temperature extremes (TXx) and warm events (TX90p/TN90p) inhibited radial growth, cold extremes (TX10p/TN10p) and increased diurnal temperature ranges (DTR) exhibited moderate growth-enhancing effects. CMIP6-based projections indicate significant future growth declines across the Altai Mountains. This study advances understanding of extreme climate impacts on forest ecosystems through a novel multi-proxy approach combining dendrochronology and remote sensing. Our findings provide scientific foundations for conservation, restoration, and adaptive management of forest ecosystems under climate change.